Depiction of Indrani on the Jangha of the Shiva Temple 2 - Temples of India Project Team (Jio Institute, 2024)
The south view of the Jangha (wall) of the Shiva Temple (Shiva Temple 2), behind the Sitaleshwar Temple has a depiction of Indrani with six arms on the kumbha (pot) moulding. In her upper hands, she holds a broken weapon and vajra (thunderbolt weapon associated with Indra), while her middle hands hold unidentified attributes. In her lower hands, she holds a kamandalu (water carrier or pot) and varadaksha (boon-granting gesture holding a rosary). At the base of her pedestal, there is an illustration of an elephant.